Real-time routing protocol with load distribution in wireless sensor network based on IEEE 802.11 and IEEE 802.15.4 - Ahmed, Adel Ali (Penerbit UTM Press, 2007)
In Wireless Sensor Network (WSN), sensors gather information about the physical world, while base station takes decisions and then perform appropriate actions upon the environment, which allows a user to effectively sense and monitor from a distance in real time. This paper proposes a novel real time routing protocol with load distribution (RTLD) that provides efficient power consumption and high packet delivery ratio in WSN. The highlight advantage of RTLD is that it can deliver packets within their end-to-end deadlines, while minimizing the network miss ratio and power consumption. It combines the geocast forwarding with link quality, maximum velocity and remaining power to achieve the real time routing in WSN. The remaining power capability assists WSN to avoid routing holes problem due to power expiration